Zero Cement Concrete with Self-Curing Technology: An Overview - Anuja, N.; Mohammed Yasar, A. (Asian Journal of Engineering and Applied Technology, 2021)
Geopolymer concrete is the concept of environmental friendly construction material which helps in reducing the greenhouse gas emission, however it cannot be applied directly on field due to its steam curing process. To overcome this defect various researcher have found self-curing or ambient curing process to achieve same strength as in steam curing process for geopolymer. This paper presents an over review about self-cured or ambient cured geopolymer concrete produced by various methods.